2020
DOI: 10.1039/d0ra07204d
|View full text |Cite
|
Sign up to set email alerts
|

Greening the synthesis of peptide therapeutics: an industrial perspective

Abstract: This review highlights the efforts made to date to promote greener peptide synthesis, from an industrial perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 189 publications
(242 reference statements)
0
44
0
Order By: Relevance
“…If these qualities are met, technical challenges in the pilot plant environment can be minimised and product output and manufacturing time kept at an acceptable level. 24,25,42 • Solvent melting point ≤ 10°C…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If these qualities are met, technical challenges in the pilot plant environment can be minimised and product output and manufacturing time kept at an acceptable level. 24,25,42 • Solvent melting point ≤ 10°C…”
Section: Resultsmentioning
confidence: 99%
“…In the search for a DMF substitute in large-scale SPPS, we have therefore decided to focus on environmental and safety aspects based on the ECHA-REACH status, and herein we define green solvents from this perspective. 21 Significant work has been done by teams in both academia and industry over the last decade in making peptide synthesis greener, [22][23][24][25] with recent focus on solvent substitution, reduction and recycling in SPPS. More benign solvents investigated for use in various stages of the SPPS process include acetonitrile (MeCN), 26,27 2-methyl tetrahydrofuran (2-Me-THF), [28][29][30][31] ethyl acetate (EtOAc), 27,29,31 anisole, 27 dimethyl carbonate (DMC), 27,31 N-butylpyrrolidone (NBP), 11,31,32 γ-valerolactone (GVL), 31,[33][34][35][36][37] cyclopentyl methyl ether (CPME), 30,31 4-methyl tetrahydropyran (MTHP), 31 and N-formylmorpholine (NFM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In recent years, this has triggered considerable research into identifying greener and less toxic alternatives to especially DMF in SPPS. [9][10][11][12] We have found that binary mixtures of green solvents (e.g. dimethyl sulfoxide (DMSO)/ethyl acetate (EtOAc), DMSO/1,3-dioxolane (DOL), and DMSO/2-methyl tetrahydrofuran (2-Me-THF) that display similar polarity and viscosity profiles to DMF are viable, less toxic solvent alternatives to DMF in SPPS.…”
Section: Introductionmentioning
confidence: 99%
“…However, this promising treatment is affected by administration issues owing to the difficulties of atrial natriuretic peptides in penetrating the cornea to lower IOP. To overcome this drawback, TAK639 was designed as a cornea-permeable CNP derivative, exhibiting increased production and cellular concentrations of cyclic guanosine monophosphate (cGMP), able to lower IOP ( Martin V. et al, 2020 ).…”
Section: Miscellaneousmentioning
confidence: 99%